M. Amin Syukur’s Socio-Sufism: Bridging Spiritual and Social Piety - Suhandi, Suhandi; Ferlitasari, Reni; Rohimah, Luthfi; Achlami, M.A. (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
The esoteric aspect of Islam, namely sufism, can provide essential values in influencing people's views and attitudes in their lives that, in turn, motivate them to achieve their goals in life as individuals and as a collective society. This study aims to analyse sufism as part of Islamic teachings, emphasising aspects of social morality (equality, compassion, mutual help, tolerance, ukhuwwah or brotherhood) initiated by M. Amin Syukur. This study applies a qualitative method using a content analysis approach. The results discovered that M. Amin Syukur promotes social sufism, i.e., sufism that concerns social life. Such sufism has characteristics, namely humane, empirical, and functional. M. Amin Syukur's Sufistic idea is rich in human values for creating social order and good community relations.Contribution: This study provides a new understanding that the function of sufism in society can be measured by its role, i.e. its contribution to society. Those who perform spiritual journey (sālik) must be active in all aspects of life, such as economy, politics, and society. Such Sufism by M. Amin Syukur is called social sufism.